Predictors of retirement security among the Malaysian civil servants - Mohd Ishak, Zalina; Magli, Amirah Shazana; Sabri, Mohamad Fazli (Human Resource Management Academic Research Society, 2022)
This research aims to determine the determinants of retirement security (RS) among Malaysian civil servants, identify the "inputs"—retirement literacy, retirement behaviour, and professional financial advice—and the "throughput"—attitudes toward retirement (ATR)—to reach the intended "outputs"—RS. Self-administered questionnaires were utilised to survey Malaysian civil servants regarding their RS. A multi-stage random sampling method was used to draw a representative sample of Malaysian civil servants and 361 completed self-administered questionnaires were received from 25 government departments in 5 regions: North, South, East, West and East Malaysia (Sabah). Covariance-Based Structural Equation Modelling statistically analysed data. With a R square of 0.42, the RS model explains 42% of retirement security variances. ATR and retirement behaviour significantly influence Malaysian civil servants' RS. Partial mediation was depicted in the influence of retirement behaviour; on RS, and full mediation was shown in the influence of retirement literacy and professional financial advice; on RS. This study could help policy-makers, government, and non-government organisations identify Malaysian civil servants' vulnerability to unsecured retirement based on socio-economic attributes and practises. These agencies could design RS programmes for Malaysian civil servants based on retirement literacy, retirement behaviour, professional financial advice, and ATR levels.